SIKAP TERHADAP SAINS SISWA DALAM PEMBELAJARAN IPA FISIKA MELALUI PENERAPAN STRATEGI INDEX CARD MATCH PADA MATERI KALOR DI KELAS VII 4 SMPN 20 PEKANBARU - Fadhil, Muhammad Yatim Fadhil Yatim; ', Azhar; ', Fakhruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The aim of this research was to determine the creasing of students' attitudes toward science Physics in class VII4 SMPN 20 Pekanbaru by implementing in learning Index Card Match strategy in heat subject. The research subjects were students of class VII4 totalling 39 people consisting of 15 male students and 24 female students. Data collection instruments in this research a question of students attitudes towards science consisting of 24 items. Analysis of the data in this research is descriptive analysis to see changes in students attitudes toward science and use the gain. From the analysis of the data showed an increase in students attitudes towards science has increased by an average of 0.31. Thus, it can be concluded that the implementation of physics learning using the Index Card Match strategy can improve students's attitudes toward science in class VII4 SMP 20 Pekanbaru.Key Words : Index Card Match strategy, students's attitudes toward science, heat